Revisiting the past as a means of validation: Bridging the myth of the resistance and the satire of the economic miracle in two comedies "Italian style" - Giacomo Boitani (Alphaville: Journal of Film and Screen Media, 2012)
Many commedia all’italiana filmmakers have acknowledged the neorealist mode of production as a source of inspiration for their practice of pursuing social criticism in realistic and satirical comedies between 1958 and 1977. The detractors of the genre, however, have accused the commedia filmmakers of “diluting” the neorealist engagement to a simple description of the habits of Italians during the Economic Miracle, a description which threatened to encourage, through the casting of popular stars, the cynical attitude it sought to satirise. In this article, I shall discuss how two commedia all’italiana directors, namely Dino Risi and Ettore Scola, produced two significant commedie, respectively Una vita difficile (1961) and C’eravamo tanto amati (1974), which bridged the Resistance setting, associated with neorealism,and the Economic Miracle setting of most commedie all’italiana in order to reaffirm their neorealist roots, thus revisiting the past as a response to the critical underestimation from which their cinematic practice suffered.